2003
DOI: 10.1002/ptr.1188
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of medicinal plant extracts against periodontopathic bacteria

Abstract: This study was performed to evaluate the antibacterial activity of Althaea officinalis L. roots, Arnica montana L. flowers, Calendula officinalis L. flowers, Hamamelis virginiana L. leaves, Illicium verum Hook. fruits and Melissa officinalis L. leaves, against anaerobic and facultative aerobic periodontal bacteria: Porphyromonas gingivalis, Prevotella spp., Fusobacterium nucleatum, Capnocytophaga gingivalis, Veilonella parvula, Eikenella corrodens, Peptostreptococcus micros and Actinomyces odontolyticus. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0
12

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(101 citation statements)
references
References 13 publications
(11 reference statements)
3
79
0
12
Order By: Relevance
“…Oral pathogens have been recently tested for antimicrobial susceptibility to a number of plant extracts and natural substances (7,8).…”
Section: Ma Botelho Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Oral pathogens have been recently tested for antimicrobial susceptibility to a number of plant extracts and natural substances (7,8).…”
Section: Ma Botelho Et Almentioning
confidence: 99%
“…The prevalence and incidence of oral diseases, coupled with the resultant social and economic implications, has led to a constant striving to produce safer substances for the development of new natural antimicrobial agents (6,7). In fact there is an overwhelming number of studies on the biological activities of plants and their natural product derivatives (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Iauk et al [21] also showed that the higher the concentrations of the Vernonia amygdalina, the larger the diameter of the bacterial growth inhibition zones.…”
Section: Discussionmentioning
confidence: 98%
“…In the Flora of Syria, this genus is represented by 8 species [1]. Previous studies demonstrated therapeutic potentialities of Calendula officinalis L. such as anti-inflammatory activity [2][3][4][5], immunomodulatory [6][7], Hepatoprotective [8], wound-healing [9], antioxidant [10][11][12], antibacterial and antiparasitic activity [13][14][15][16]. The essential oil from C. officinalis has been also investigated [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%